Revival of the concept and development of donation after human circulatory death in the era of organ transplantation - V. O. Tumanskyi; S. I. Vorotyntsev; L. M. Tumanska (Zaporozhye State Medical University, 2020)
Since the beginning of the twentieth century, in parallel with the standards of the whole brain death and the brain stem death of a donor used in transplantology, the concept of donation after human circulatory death has received a practical revival. Aim: analysis of the revival of the concept of circulatory death of a person and donor protocols after its ascertaining. The review analyzes retrospective data on the development of the concept of circulatory death of a person, widely used in modern transplantology. It has been established that the main criteria for human circulatory death, adopted in all countries with active organ transplantation programs, are the patient's loss of blood circulation and breathing. The features of donor protocols after controlled and uncontrolled circulatory death, donation after euthanasia, modern technologies of explantation and preservation of donor organs, as well as moral and ethical problems associated with controlled donation after circulatory death are defined. Conclusion. The widespread donation after the patient's circulatory death led to significant success in transplantation of kidneys, lungs, liver, pancreas and heart.